The Novelty-Seeking Phenotype Modulates the Long-Lasting Effects of Intermittent Ethanol Administration during Adolescence - Montagud-Romero, Sandra (Public Library of Science, 2014)
The aim of the present study was to investigate if a novelty-seeking phenotype mediates the long-lasting consequences of intermittent EtOH intoxication during adolescence. The hole board test was employed to classify adolescent mice as High- or Low-Novelty Seekers. Subsequently, animals were administered ethanol (1.25 or 2.5 g/kg) on two consecutive days at 48-h intervals over a 14-day period. Anxiety levels - measured using the elevated plus maze- spontaneous motor activity and social interaction test were studied 3 weeks later. A different set of mice underwent the same procedure, but received only the 2.5 g/kg dose of ethanol. Three weeks later, in order to induce CPP, the same animals were administered 1 or 6 mg/kg of cocaine or 1 or 2.5 mg/kg MDMA. The results revealed a decrease in aggressive behaviors and an anxiolytic profile in HNS mice and longer latency to explore the novel object by LNS mice. Ethanol exposure enhanced the reinforcing effects of cocaine and MDMA in both groups when CPP was induced with a sub-threshold dose of the drugs. The extinguished cocaine-induced CPP (1 and 6 mg/kg) was reinstated after a priming dose in HNS animals only. Our results confirm that intermittent EtOH administration during adolescence induces long-lasting effects that are manifested in adult life, and that there is an association between these effects and the novelty-seeking phenotype.